Criminal Records Information Management System for Kabale Central Police Station. - Munialo, Rogers (Kabale University, 2025)
This report presents the development of a web-based Criminal Record Information Management System (CRIMS) for Kabale Central Police in Uganda. The system aims to improve the management and retrieval of criminal records, enhancing the efficiency and effectiveness of police operations. The paper begins with an introduction, and a literature review, followed by a description of the methodology used in the system's development. The system design, implementation, and testing are then presented, highlighting the key features and functionalities of the CRIMS. The results show a significant improvement in data management and retrieval, with the system meeting the requirements of the police department. The paper concludes with recommendations for future enhancements and potential applications of the system in other law enforcement agencies. The developed CRIMS has the potential to revolutionize criminal records management in Police, promoting informed decision-making and crime reduction.